INFLUENCE OF MUSIC PREFERENCES ON ANGER LEVELS AMONG COLLEGE STUDENTS: AN ANALYTICAL STUDY - CV, Chunmithra; R.A., Ghayathri Swetha Kumari (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present study aims to study the impact of music preferences on anger levels amongst undergraduate and postgraduate students. A survey was administered online (via Google Forms) and offline to a sample of 210 individuals using convenience and snowball sampling methods. Two tools were utilised in the questionnaire - the Music Preference Scale developed by Upadhyay and colleagues and the Behavioural Anger Response Questionnaire. The responses were computed in the form of the respective subscales and dimensions of each scale. The Music Preference Scale recorded readings under five dimensions - Intense and Electrical, Devotional and Cultural, Emotional and Melodious, Reflective and Spiritual, and Contemporary and Rhythmic. The Behavioural Anger Response Questionnaire assesses anger across 6 domains - Direct Ager Out, Rumination, Social Support Seeking, Diffusion, Assertion and Avoidance. Data was analysed using descriptive statistics - to analyse the demographics of the sample; T-test to test significance of the collected data, and Pearsons’ Correlation analysis has been conducted to study the relationship between the two variables. According to the results of the study, there is no significant difference in the anger levels expressed by males and females, or by undergraduate and post- graduate students. Males & females seemed to listen to the same level of Intense & Electronic, Contemporary & Rhythmic, Spiritual & Reflective music. Females were found to listen to more Devotional & Cultural and Emotional & Melodious music. Qualitative analysis shows no significant difference in the preference for music genres amongst undergraduate and post-graduate students. To conclude, music preferences have a negligible impact on anger levels.